THEORETICAL PRINCIPLES AND FOREIGN EXPERIENCES OF THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP (Marketing Journal, 2025)
Small business and private entrepreneurship play a crucial role in the sustainable development of the national economy. This article analyzes effective strategies for supporting and developing small businesses based on the experiences of the USA, Germany, Japan, South Korea, and the United Kingdom. Additionally, the significance of small businesses in Uzbekistanʼs economy and the existing opportunities for their growth are examined. A SWOT analysis is conducted to assess the strengths, weaknesses, opportunities, and threats facing small businesses. The research findings indicate that improving legal, financial, and innovative support mechanisms can contribute to economic growth. 69
Keywords: small business; private entrepreneurship; economic development; foreign experience; government support; SWOT analysis; innovation; financing